Studi perbandingan beban hidup pada peraturan pembebanan jembatan jalan raya - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Psikologi Universitas Gadjah Mada, 1998)
ABSTRACT In Indonesia, design load for bridge deck is 20 ton per axle, while for the beam 8 kN/m2 (uniform load up to 30 m span) and 44 kN/m (line load) should be applied. The latest 2 loads are approximately equivalent to 20 ton per axle. If the load exceeds the capacity, then the rate of damage of bridge will be exaggerated. This phenomenon happens now in Indonesia. An analysis to evaluate the existing standard of bridge loading is needed. The analysis is done by comparing the live load according to the code of the highway bridge loading in Indonesia and USA (AASHTO), England (British Standard Institution), German (DIN 1072) and Japan (Japan Road Association). There are two codes Indonesia, the Highway Bridge Loading (PPPJJR) 1987 and Bridge Management System 1992. The analysis includes the calculation of moment and shear of a simple beam bridge, according to the code of the observed countries. The result are presented graphically. Up to 60 m of bridge-span, the moment due to live load (with impact according to PPPJJR /987) is higher than those in USA and Japan (for 30 m to 55 m span), but it is lower than BMS 1992, Germany and England (from 20 m span). The shear due to live load (with impact) according to PPPJJR 1987 is higher than those in USA, but lower than those in BMS 1992, Germany, Japan and England (from 20 m span). The moment and shear due to live load (without impact) according to PPPJJR 1987 is higher than those in USA, Japan and BMS 1992 (for 35 m to 55 m span), but lower than those in Germany.